A study of the differentiation and dedifferentiation of three human melanoma cell lines - Davids, Lester Merlin (Department of Human Biology, 2017)
Pigment formation in melanocytes is the end-point of a series of biochemical reactions involving numerous melanocyte-specific proteins including, inter alia, the enzymes tyrosinase, tyrosinase-related protein-1 (TRP-1 ), tyrosinase-related protein-2 (TRP-2) and the melanosomal protein encoded by the P gene. The function of tyrosinase and TRP-2 have recently been clarified, but the roles of TRP-1 and the P protein remain unknown. The first aim of this study was to examine the expression of these proteins at a transcriptional and translational level in order to provide more insight into possible mechanisms which may lead to changes in melanoma cell differentiation. Three human melanoma cell lines (Mel 1, Mel-2 and Mel-3) with varying levels of pigmentation (highly melanised to amelanotic) were examined by enzyme assays and RNA quantification methods. The results showed gene expression of all four genes in the highly melanised Mel-1 and amelanotic Mel-3 cell lines. TRP-1 and TRP-2 were not expressed in the melanised Mel-2 cell line. These results suggest that there is no correlation between tyrosinase gene expression and level of pigmentation in these cell lines. In addition, they show that the level of pigmentation of human melanoma cell does not necessarily correlate to the level or pattern expression of the tyrosinase gene family. Furthermore the results of the present study show that the P gene is expressed at high levels in all the melanoma cell lines, irrespective of their level of pigmentation . The second broad aim of this study was to determine the effect of melanocytestimulating hormone (a melanogenic stimulator) on melanogenesis in Mel-1 cells. Mel-1 cells, which were exposed to 10⁻⁷ M MSH for 6 days, showed no change in tyrosinase mRNA levels, but the mRNA levels of TRP-1, TRP-2 and the P gene were reduced. This suggested the presence of a possible co-ordinated down-regulatory mechanism in the Mel-1 cells under the influence of MSH.